2014
DOI: 10.3349/ymj.2014.55.2.353
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Coronary Perfusion after Occlusion of Coronary Arteries in Kawasaki Disease

Abstract: PurposeMyocardial infarction in children with total occlusion of a coronary artery after Kawasaki disease is rare due to multiple collateral vessels. We aimed to investigate the changes in coronary perfusion associated with coronary artery occlusion after Kawasaki disease.Materials and MethodsEleven patients with coronary artery occlusion after Kawasaki disease were investigated. Serial coronary angiographies after total occlusion of a coronary artery were reviewed and the changes were described in all patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
(24 reference statements)
0
5
0
1
Order By: Relevance
“…At the same time, there are known a great variety of different conditions that might lead to an MI in other age groups, including Kawasaki disease [11], aortoarteritis, myocarditis, familial hypercholesterolemia, inherited arteriopathy, primary cardiomyopathy, systemic vasculitis involving the coronary arteries, drug addiction, nephrotic syndrome, storage disease, progeria, sespsis, neoplastic processes [12]. These diseases were not found in our patient after full clinical, laboratory and instrumental studies.…”
Section: Discussionmentioning
confidence: 71%
“…At the same time, there are known a great variety of different conditions that might lead to an MI in other age groups, including Kawasaki disease [11], aortoarteritis, myocarditis, familial hypercholesterolemia, inherited arteriopathy, primary cardiomyopathy, systemic vasculitis involving the coronary arteries, drug addiction, nephrotic syndrome, storage disease, progeria, sespsis, neoplastic processes [12]. These diseases were not found in our patient after full clinical, laboratory and instrumental studies.…”
Section: Discussionmentioning
confidence: 71%
“…Based on this experience, we previously suggested that the status of collaterals associated with TO of coronary arteries in KD should be evaluated regularly for the prevention of further MI. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Patients with CAL were found to have increased levels of cytokines, compared to those with normal coronary arteries 23. These cytokines may mediate vascular damage and lead to CAL in KD 29. In an experimental study, high-dose IVIG inhibited the activation of monocytes, macrophages, and coronary arterial endothelial cells, whereas dexamethasone inhibited these cells, in addition to T cells, in vitro 11.…”
Section: Discussionmentioning
confidence: 99%